Greece : Selected Issues. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1999)
This Selected Issues paper and Statistical Appendix presents a number of studies designed to probe in more depth issues of fiscal adjustment, the public sector's creditworthiness as judged by foreign lenders, and the banking system in Greece. The paper highlights that fiscal adjustment in Greece has followed a gradual path, relying to a significant extent on revenue enhancement and eschewing primary expenditure reduction. The paper also examines the evolution and tax determinants of the most widely followed indicator of the health and competitiveness of a banking system-the lending-deposit spread.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet